Exercise and calcium supplementation: Effects on calcium homeostasis in sportswomen - Martin, B. R.; Davis, S.; Campbell, W. W.; Weaver, C. M. (Medicine & Science in Sports & Exercise, 2007)
Purpose: Exercise-induced sweat calcium losses have been reported as substantial in male athletes. The first aim of the study was to quantify the increase in 24-h total dermal calcium losses and the net changes in calcium retention in active sportswomen after a 1-h strenuous exercise session. A second aim was to determine the effectiveness of calcium supplementation to offset any calcium loss.